Promoting our Colleagues’ Wellbeing: Group Work during the Covid Pandemic - Molyn Leszcz (Forum for Group Psychotherapies and Processes)
As a Canadian, I want to make special note and express appreciation today that right now in Canada, Pope Francis is on a mission of reconciliation and repair with the Canadian indigenous communities, who have been harmed and traumatized by the Canadian residential school system. His visit is the opportunity for great healing.